CD43 in the nucleus and cytoplasm of lung cancer is a potential therapeutic target. Issue 8 (29th October 2012) - Fu, Qiangwei; Cash, Steven E.; Andersen, Jeremiah J.; Kennedy, Colin R.; Oldenburg, Darby G.; Zander, Valerie B.; Foley, Greta R.; Simon Shelley, Carl
Abstract CD43 is a transmembrane sialoglycoprotein. Normally the molecule is only produced by white blood cells where it regulates functions such as intercellular adhesion, intracellular signaling, apoptosis, migration and proliferation. Two CD43 antibodies were used to interrogate 66 cases of non‐small cell lung cancer (NSCLC) and 24 cases of small cell lung cancer (SCLC). In addition, we engineered the CD43‐positive lung cancer cell line A549 to stably express either non‐targeted or CD43‐targeted small‐interfering RNA (siRNA). These lines were then subjected to in vitro assays of apoptosis, natural killer (NK) cell cytotoxicity, intercellular adhesion and transendothelial migration. A xenograft mouse model evaluated the ability of the lines to grow primary tumors in vivo. CD43 was found to be expressed in the majority of both SCLC and NSCLC. Inclusive of CD43‐negative tumors, differential patterns of nuclear and cytoplasmic expression of CD43 define four molecular subcategories of lung cancer. Targeting CD43 in A549 lung cancer cells, increased homotypic adhesion, decreased heterotypic adhesion and transendothelial migration, increased susceptibility to apoptosis and increased vulnerability to lysis by NK cells. Furthermore, targeting inhibited the growth of primary tumors in nude mice.